Quantum fluctuations increase the self-diffusive motion of para-hydrogenin narrow carbon nanotubesw - Kowalczyk, Piotr; Gauden, P.; Terzyk, A.; Furmaniak, S. (Royal Society of Chemistry, 2011)
Quantum fluctuations significantly increase the self-diffusive motion of para-hydrogen adsorbed in narrow carbon nanotubes at 30 K comparing to its classical counterpart. Rigorous Feynman’s path integral calculations reveal that self-diffusive motion of para-hydrogen in a narrow (6,6) carbon nanotube at 30 K and pore densities below ~29 mmol cm-3 is one order of magnitude faster than the classical counterpart. We find that the zero-point energy and tunnelling significantly smoothed out the free energy landscape of para-hydrogen molecules adsorbed in a narrow (6,6) carbon nanotube. This promotes a delocalization of the confined para-hydrogen at 30 K (i.e., population of unclassical paths due to quantum effects). Contrary the self-diffusive motion of classical para-hydrogen molecules in a narrow (6,6) carbon nanotube at 30 K is very slow. This is because classical para-hydrogen molecules undergo highly correlated movement when their collision diameter approached the carbon nanotube size (i.e., anomalous diffusion in quasi-one dimensional pores). On the basis of current results we predict that narrow single-walled carbon nanotubes are promising nanoporous molecular sieves being able to separate para-hydrogen molecules from mixtures of classical particles at cryogenic temperatures.